Conjugates of Pyropheophorbide a with 17-Substituted Steroidal Androgens. Synthesis, Molecular Modeling, Interaction with Some Cancer Cells - Zolottsev, V.A.; Korolchuk, A.M.; Lukin, A.S.; Morozevich, G.E.; Mekhtiev, A.R.; Novikov, R.A.; Tkachev, Y.V.; Suvorov, N.V.; Misharin, A.Y. (Biomedical Chemistry: Research and Methods, 2022)
Five new bifunctional conjugates of pyropheophorbide a with 17-substituted testosterone, dihydrotestosterone and epitestosterone differing in the length of linker (1 – 5) and two new complex conjugates 6 and 7 (containing three functional units: pyropheophorbide a, 17α-substituted testosterone, and lipophylic hexadecyl chain, connected with L-lysine joining block) were synthesized. Mutual influence of steroidal and macrocyclic fragments in conjugates (1 – 7) was established by analysis of 1H NMR spectra and molecular models of conjugates. Studies of interaction of conjugates 1 – 5 with prostate carcinoma cells revealed that their uptake and internalization were dependent on the structure of conjugates, particularly on the stereochemical configuration of 17-hydroxyl group in steroidal moiety, and the length of linker connecting pyropheophorbide a with steroid fragments. Conjugates 1 – 5 significantly decreased the growth and proliferation of LNCaP and PC-3 cells. The highest anti-proliferative activity demonstrated by epitestosterone derivative 3, comprising short linker. Irradiation of labeled cells with light (λ = 660 nm) was significantly increased cytotoxicity. Trifunctional conjugates 6 and 7 easily formed mixed micells with phosphatidyl choline and pluronic F68; these mixed micelles efficiently internalized by human hepatocarcinoma Hep G2 cells. The binding of conjugates 6 and 7 in the form of mixed micelles to Hep G2 cells depended on the conjugate structure, rather than on the method of solubilization.